Motivations and incentives for mechanization in Zambia: A mixed methods analysis - Mulungu, Kelvin Hicingabula; Ngoma, Lushomo Molly; Rumbidzai Mhembere; Manyanga, Mark; Simutowe, Esau; Thierfelder, Christian L.; Md Abdul Matin; Ngoma, Hambulo (International Maize and Wheat Improvement Center, 2024)
This study examines smallholder farmers' preferences for ownership models and mechanization in Zambia using mixed methods from a quantitative survey of 208 farmers, 18 focus group discussions, and 28 key informant interviews from farmers who own mechanized equipment. Productivity enhancement and income generation motivated tractor ownership. Being a male farmer is correlated with preference for an individual ownership model over group ownership. Female-headed households and increase in oxen owned is associated with preference for group ownership and individual ownership, respectively. Risk-contingent credit (RCC), and RCC combined with repair insurance were the most preferred incentives, highlighting farmers' need for comprehensive risk management in mechanization investments.